Situational analysis of rashtriya kishor swasthya karyakram at one of the districts of Gujarat - Tejas Shah; Bipin Prajapati; Venu Shah (Wolters Kluwer Medknow Publications, 2022)
Background: Rastriya Kishor Swasthya Karyakram (RKSK) is a holistic approach implemented for betterment of adolescent health. Barriers in the implementation can be identified by conducting the situational analysis of any program. The present study is a part of the multi-centric study conducted at Sabarkantha district for situational analysis of RKSK. To assess the implementation of various components under RKSK at various levels of health facilities, 2) to identify the barriers faced by services providers in RKSK implementation, and 3) to identify the perception of beneficiaries regarding RKSK. Materials and Methods: A Cross-sectional study using a mixed method approach was conducted to review the implementation of the RKSK program at Sabarkantha district. In-depth interview of health personnel involved in implementation of RKSK was conducted using pre-structured and pre-tested interview guide. Ongoing sessions of Adolescent Friendly Health Clinics (AFHCs) were examined, and exit interview of adolescents was conducted. Adolescents residing within limits of the defined facility were also interviewed. Frequency and percentages were used for descriptive analysis, and a thematic qualitative analysis approach was used for qualitative aspects. Results: RKSK was implemented successfully at Primary Health Centers. Infrastructure for AFHC was inadequate particularly at higher care facilities. Weekly Iron Folic Acid Supplementation (WIFS) was successfully implemented in the district. Overall sessions conducted at AFHC were found to be satisfactory. Adolescents interviewed in the community were satisfied with the services delivered to them under RKSK. Conclusion: For better implementation of RKSK, there is a need to focus on certain issues such as inadequate infrastructure of AFHCs, the lack of trained counselors, unavailability of sanitary pads, and inadequate participation of adolescents from the community in availing RKSK services.